The Platform Construction of High-power Electronic Devices Industrialization - 丁荣军; 张明; 黄建伟 (机车电传动)
Make a detailed statement of the platform construction of high-power electronic devices industrialization, expound the device structure design, process capability and product testing, product application support and other aspects, and put forward an idea that to get a real industrialization breakthrough, a system design for those aspects is necessary.